2020
DOI: 10.1111/bju.15171
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract stone deaths: data from the Australian and New Zealand Audits of Surgical Mortality

Abstract: , and identify common causes, clinical management issues (CMIs), and areas for improvement. Patients and Methods All urological-related deaths reported to the Australian and New Zealand Audit of Surgical Mortality (ANZASM) from 2009 to 2017 were analysed. The Bi-National Audit of Surgical Mortality (BAS) database was interrogated for any involvement with renal, ureteric or bladder stones and all relevant associated data analysed. Any CMIs documented by the peer reviewers were recorded and compared to those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The impact of the inappropriate management of urinary stones can have a dramatic impact on patients’ safety. As reported by Galiabovitch et al [ 12 ], approximately 10% of all surgical deaths are secondary to stones. Also, urinary sepsis are demonstrated to be responsible for 49.5% of all deaths.…”
Section: Discussionmentioning
confidence: 88%
“…The impact of the inappropriate management of urinary stones can have a dramatic impact on patients’ safety. As reported by Galiabovitch et al [ 12 ], approximately 10% of all surgical deaths are secondary to stones. Also, urinary sepsis are demonstrated to be responsible for 49.5% of all deaths.…”
Section: Discussionmentioning
confidence: 88%
“…From these results it can be seen that URS consumes many hospital resources, has a 10% complication rate and a stone‐free rate of less than 40%, when reviewed. With urinary tract stones accounting for almost 10% of all urological related deaths in Australia, a number of which can be attributed to clinical management issues during URS, 16 we would suggest that all patients with renal tract stones should be discussed at a regular stone meeting to ensure consistency in treatment and adherence to guidelines. Furthermore, follow‐up appointments with stone analysis and imaging should be made mandatory practice and incorporated into local guidelines to ensure that all patients have adequate follow‐up to ensure complete resolution of disease.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been no comprehensive review of factors associated with death after thyroid, parathyroid, and adrenal surgery. The Australian and New Zealand Audit of Surgical Mortality (ANZASM) has been used to examine trends in mortality across various surgical specialties, including neurosurgery 2 , cardiothoracic surgery 3 , urology 4 , 5 , and general surgery 6 , 7 . These studies have demonstrated that, by examining the small subset of operations resulting in patient death, potential gaps and pitfalls in clinical management may be identified to direct future improvement strategies in the quality and safety of surgical care.…”
Section: Introductionmentioning
confidence: 99%